Association between Atrial Fibrillation and Risk of Alzheimer’s Disease and Vascular Dementia: A Systematic Review and Meta-analysis - Yi Zheng; Guangping Li (Annals of Indian Academy of Neurology)
Background and Objectives: Recent research suggests that atrial fibrillation (AF) may influence the risk of developing Alzheimer’s disease (AD) and vascular dementia (VaD). However, existing studies have provided inconsistent results, with some showing a significant association between AF and the risk of AD and VaD, while others do not. The objective of this study is to conduct a meta-analysis to investigate the association between AF and the risk of AD and VaD. Methods: A comprehensive search was conducted in several databases, including PubMed, Web of Science, Embase, and Google Scholar, covering research published before December 2023. Odds ratios (ORs) or relative risks (RRs) and 95% confidence intervals (CIs) were calculated using Stata 12.0 software to assess the association between AF and the risk of AD or VaD. Results: The meta-analysis revealed a significant association between AF and an increased risk of AD, using a random effects model (OR/RR: 1.23, 95% CI: 1.13–1.34, I2 = 81.3%, P < 0.001). Similarly, a significant association was found between AF and an increased risk of VaD, using a random effects model (OR/RR: 1.80, 95% CI: 1.57–2.07, I2 = 82.1%, P < 0.001). Conclusion: In summary, our comprehensive meta-analysis provides compelling evidence of a significant association between AF and an elevated risk of AD and VaD. The findings are corroborated by robust cross-sectional and longitudinal cohort studies, which further validate the observed link. However, further large-scale prospective studies are necessary to comprehensively investigate the relationship between AF and the risk of AD and VaD.